Electrochemical On‐Site Switching of the Directional Liquid Transport on a Conical Fiber. Issue 24 (12th May 2022) - Xu, Bojie; Chen, Xuan; Shi, Zhongyu; Meng, Lili; Wang, Dong; Jiang, Lei; Liu, Huan
Abstract: Directional liquid transport (DLT), especially that proceeding on a conical fiber (DLT‐CF), is an important mass‐transfer process widely used both by natural organisms and in practical applications. However, on‐site switching of the DLT‐CF remains a challenge due to the nontunable driving force imparted by the structural gradient, which greatly limits its application. Here, unprecedently, a facile electrochemical strategy is developed for reaching the on‐site switchable DLT‐CF, featuring in situ control and fast response. Depending on the poised electric potential, the droplet can either move directionally or be pinned at any position for a tunable duration time, exhibiting completely different moving characteristics from the traditional DLT‐CF with no control. It is proposed that the surface hysteresis resistance, closely related to both the surface hydrogen‐bonding network and the droplet topology on the fiber, can be largely altered electrochemically. The tunable hysteresis resistance works synergistically with the conical‐structure‐induced Laplace pressure to on‐site tune the forces acting on the droplet, leading to various controllable DLTs‐CF, including those with tunable distance and direction, array manipulation, and assembly line processing of droplets. The strategy is applicable for versatile liquids, offering a general approach for controllable liquid transport in fibrous systems. Abstract : On‐site switchable directional liquid transport on a conical fiber (DLT‐CF) is realized by a facile electrochemical strategy. The droplet dynamic on a conical fiber can be switched between moving and pinning by applying and removing an electric potential. Taking advantages, various controllable DLT‐CFs are demonstrated, including those with tunable transport distance, array manipulation, and assembly‐line processing.